Telling Tales Testing Boundaries: The Radicalism of Kerstin Ekman’s Norrland - Forsås-Scott, Helena (Journal of Northern Studies, 2014)
Beginning with analyses of De tre små mästarna (1961) [Under the Snow] and Händelser vid vatten (1993) [Blackwater], this investigation into the representation of Norrland in the prose fiction of Kerstin Ekman draws on theoretical material by, among others, Umberto Eco, Mieke Bal, and Rosi Braidotti. The study revolves around the ways in which the texts are told and, especially, who is seeing the events narrated and the implications of this. The juxtaposition of different focalisers in Blackwater helps engage the reader in the novel’s central questions about memory, identity, environmental destruction, and interpretation. With the central character a troll from the forest, Rövarna i Skuleskogen (1988) [The Forest of Hours] develops a far-reaching critique of the western categories and boundaries used to determine what is ‘human’ and what is ‘animal’. In the trilogy The Wolfskin, consisting of Guds barmhärtighet (1999) [God’s Mercy], Sista rompan (2002) [‘The Last String’] and Skraplotter (2003) [‘Scratch Cards], a plot covering the whole of the twentieth century is focalised by a number of characters and involves the reader in issues to do with postcolonialism, environmentalism and ethics.